A Study on the Relationship between CDS Premiums and Stock Market Indices: A Case of the Fragile Five Countries - Nuri Avsarligil; Emre Turgut (Istanbul Business Research (IBR), 2021)
International investors should have a pioneering knowledge of the country's risk level before investing their savings in a country. For this purpose, Credit Default Swap (CDS) Agreements that serve as insurance against investor's risk of not collecting their receivables have been developed. These contract premiums are called CDS premiums. The relationship between the Fragile Five countries' CDS premiums and the stock market index prices has been examined by various researchers. The present study is unique because it is one of the pioneering studies examining the relationship between the CDS premiums of the Fragile Five countries and their Stock Market Indices. First, augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) unit root tests were performed for this purpose. Then, the Granger Causality test, Johansen Cointegration, and Pearson Correlation analyses were conducted to reveal the relationship between two variables. The results obtained in the study indicated that for India and Turkey, among the Fragile Five, there was a causality relationship between the stock market indices and the CDS premiums, a short-term relationship. In addition, there was a long-term cointegration relationship between the CDS premiums and the stock market indices of Turkey.
Keywords: 650; Credit default swap; Causality; Cointegration; Financial risk; Correlation